Inferior oblique weakening surgery on ocular torsion in congenital superior oblique palsy - Lee, Jinho (Int J Ophthalmol, 2015)
AIM: To investigate changes in fundus excyclotorsion after inferior oblique myectomy or myotomy. METHODS: The records of 21 patients undergoing strabismus surgery by a single surgeon between 2009 and 2012 were examined. Only patients who had undergone an inferior oblique myectomy or myotomy, with or without horizontal rectus muscle surgery, were evaluated. Digital fundus photographs were obtained, and the angle formed by a horizontal line passing through the optic disc center and a reference line connecting the foveola and optic disc center was measured. Associated clinical factors examined include age at the time of surgery, presence or absence of a head tilt, degree of preoperative vertical deviation, torsional angle, inferior oblique muscle overaction/superior oblique muscle underaction, and surgery laterality. Whether the procedure was performed alone or in combination with a horizontal rectus muscle surgery was also examined. RESULTS: Mean preoperative torsional angle was 12.0±6.4°, which decreased to 6.9±5.7° after surgery (P<0.001, paired t-test). Torsional angle also decreased from 15.1±7.0° to 6.2±4.3° in the myectomy group (P<0.001, paired t-test) but there were no significant changes in the myotomy group (P=0.093, Wilcoxon signed rank test). Multivariable linear regression analysis showed that preoperative torsional angle, degree of inferior oblique overaction, and age at surgery independently and significantly affected postoperative torsional angle. CONCLUSION: Mean torsional angle decreased after inferior oblique myectomy. Degree of preoperative torsional angle, inferior oblique overaction, and age at surgery influence postoperative torsional angle.